Data Journalism in the age of RTI - Kumar, P Praveen; ., Mangaiyarkarasi (Journal of Advanced Research in Journalism & Mass Communication, 2018)
With the rise of democracy, the modern governments have slowly started opening themselves to the idea of open governance, i.e., a transparent and accountable governance. Several legislative patterns around the world are the proof of this paradigm. The Indian government after some amount of reluctance dipped its toes with the introduction of the Right to Information Act, 2005. This has added a new requirement to the journalist’s profession – Data Crunching. After slowly understanding the plethora of stories hidden underneath these data, the Journalists have started hunting for data that they can use in their stories. Other than this, RTI has also paved way for the media organizations to serve the public interest better with data journalism. However, the data journalism comes with a huge barrier – the lack of familiarity about how to work with the data and the dearth of computing skills are the foremost of them. This paper tries to understand the possible paradigms and viability of data journalism in the Indian Journalism. How to cite this article: Kumar PP, Mangaiyarkarasi. Data Journalism in the age of RTI. J Adv Res Jour Mass Comm 2018; 5(4): 92-95.